COST-EFFECTIVENESS OF INTERVENTIONS BASED ON PHYSICAL ACTIVITY IN THE TREATMENT OF CHRONIC CONDITIONS: A SYSTEMATIC LITERATURE REVIEW. (9th October 2018) - Guillon, Marlène; Rochaix, Lise; Dupont, Jean-Claude K.
Abstract : Objectives: The aim of this study is to review evidence on the cost-effectiveness of exercise-based interventions in the treatment of chronic conditions a decade after the publication of Roine et al. in 2009 (Roine E, Roine RP, Räsänen P, et al. Int J Technol Assess Health Care . 2009;25:427–454). Methods: We carried out a review of published articles in PUBMED and JSTOR between January 1, 2008, and December 31, 2016. Full economic evaluations of exercise programs targeting patients with a chronic condition were eligible for inclusion. Data on program, design, and economic characteristics were extracted using a predefined extraction form. The quality of the economic evaluations was appraised using the adjusted Consensus Health Economic Criteria List. Results: A total of 426 articles were identified and thirty-seven studies were selected. Eleven studies dealt with musculoskeletal and rheumatologic disorders, ten with cardiovascular diseases, six with neurological disorders, three with mental illnesses, three with cancers, and four with diabetes, respiratory diseases, or pelvic organ prolapse. In total, 60 percent of exercise programs were dominant or cost-effective. For musculoskeletal and rheumatologic disorders, 72 percent of programs were dominant or cost-effective while this was the case for 57 percent of programs for cardiovascular diseases using a nonsurgical comparator. Conclusions: There is clear evidence in favor of exercise-based programs for the treatment of musculoskeletal and rheumatologic disorders and, to a lesser extent, for the treatment of cardiovascular diseases. More research is needed to evaluate the cost-effectiveness of physical activity in the treatment of neurological disorders, mental illnesses, cancers, respiratory diseases, and diabetes/obesity.